5510 SAYILI KANUNA GÖRE SOSYAL GÜVENLİK KURUMUNUN PRİM ALACAKLARINDA ZAMANAŞIMI - (:unkn) unknown (My University, 2014)
5510 sayılı Kanunda Kurum alacakları açısından özel bir zamanaşımı hükmü öngörülmüştür. Bu düzenleme uygulamada bazı sorunlara yol açmaktadır ve zamanaşımını ortadan kaldıracak bir içeriğe sahiptir. Çalışmamızda Kurum alacaklarında zamanaşımı konusunda hem 5510 sayılı Kanundan önceki düzenlemeler, hem de 5510 sayılı Kanunda öngörülen sistem üzerinde durulmaktadır.

With the law no 5510, it is arranged that a specific period of limitation provision about Institution claims. This regulation leads to some problems in practise and has a content which will be eliminate the period of limitation. The aim of this study is to emphasize both regulations which are before the law no 5510 and the system which is predicted in the law no 5510 about the period of limitation of institution claims.
Limitations at Premium Claim of Social Security Institution According to Law No 5510
Keywords: Hukuk